A method for predicting the surface quality of anodized aluminum

By using conductivity or metal structure tests before anodized aluminum, we can predict whether there will be color difference defects after anodization, which solves the problem of difficult to predict color difference defects in the existing technology, and achieves faster and more efficient detection. Avoid material waste and improve yield.

CN115125598BActive Publication Date: 2025-02-07CHINALCO HENAN LUOYANG ALUMINUM FABRICATION CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210804653.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-08
Publication Date
2025-02-07
Estimated Expiration
2042-07-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively predict whether there will be color defects on the surface of anodized aluminum materials, which will cause time-consuming and high-cost detection and correction after anodized treatment.

Method used

Before anodizing treatment, a four-probe conductivity meter is used to detect the conductivity of the aluminum material or test its metal structure to predict whether it will have color difference defects after anodizing. Specific methods include calculating the mean and extreme differences in conductivity, or testing the grain morphology to determine whether the conditions of equiaxed crystal and average grain size <50μm are met.

Benefits of technology

It realizes rapid and efficient prediction of whether the surface of aluminum will have color defects before anodizing treatment, avoids material waste, improves industrial yield, and is suitable for exterior decorative parts for automotive decoration, curtain wall panels and consumer electronics products. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115125598B_ABST
    Figure CN115125598B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for predicting the surface quality of anodized aluminum materials. It is based on the mean value of the electrical conductivity of the aluminum material before anodization and its extreme value or metal structure, and it is pre-judged whether the aluminum material has color difference defects on the surface after anodizing. The patented method constructs the correlation between the metal structure-electrical conductivity-anodized color difference of 5000 series aluminum materials with a Mg content of 0.5-6.0wt.%. Under the condition of certain anodizing parameters, the aluminum material metal structure is equiaxed crystal, the mean value of electrical conductivity satisfies 19.0-26.5MS / m, and the extreme value of electrical conductivity is <0.5MS / m. Then, the surface color difference ΔE of the aluminum material after anodizing is <0.25, and its surface quality meets the requirements. The prediction method of the present invention is suitable for aluminum materials used for appearance decorative parts of products such as automobile decoration, curtain wall panels, and consumer electronics, and has fast detection speed and high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aluminum alloy materials, in particular to a method for predicting the surface quality of anodized aluminum materials. Background Art

[0002] Aluminum alloy has good strength and thermal conductivity. Aluminum alloy that has been anodized has good wear resistance and corrosion resistance. After coloring, the appearance can present a variety of colors, which enhances the artistic and technological sense of the appearance parts. It is suitable for automotive interior parts and structural appearance parts of consumer electronic products.

[0003] As the appearance of the product, the surface quality requirements of anodized aluminum are very high, and any degree of color difference defects are not allowed. Color difference defects are the color differences on the surface of aluminum after anodizing. The color difference defects are distributed in stripes along the processing direction of the aluminum, with a width of 0.05 to 5mm and a length of several millimeters or even more than ten millimeters. It is difficult to distinguish under natural light. When observing against the light source, the heterochromatic area is darker than the normal area. The color difference defects after coloring are more obvious. It mainly depends on the experience of technicians to distinguish heterochromatic defects with naked eyes, which seriously restricts the application and promotion of anodized aluminum in the fields of automobiles and consumer electronics.

[0004] The national standard "GB T 12967.6-2008 Test methods for anodized films of aluminum and aluminum alloys Part 6: Visual observation method for testing color difference and appearance quality of colored anodized films" stipulates the test method for color difference and appearance quality of colored anodized films of aluminum and aluminum alloys, but the method adopted also relies on the naked eye detection of observers and is only applicable to the entire area of ​​the sample.

[0005] Color difference defects occur after anodizing, which is close to the final process of the product. Once the defect is discovered, it is time-consuming and costly. Therefore, it is urgent to provide a method to predict whether aluminum materials will have color difference defects after anodizing before anodizing. Summary of the invention

[0006] In order to solve the deficiencies in the prior art, the present invention provides a method for predicting the surface quality of anodized aluminum materials. The method predicts whether color difference defects will occur in the aluminum materials after anodizing by testing the electrical conductivity or metal structure of the aluminum materials before anodizing.

[0007] In order to achieve the above object, the specific scheme adopted by the present invention is:

[0008] A method for predicting the surface quality of anodized aluminum material, the method being any one of the following two:

[0009] The first method: Use a four-probe conductivity meter to detect the conductivity of different areas of the same aluminum material to be tested, and calculate the conductivity mean A and conductivity range B based on the obtained conductivity values. If A and B meet the following conditions: 19.0MS / m≤A≤26.5MS / m, B<0.5MS / m, it indicates that the surface quality of the aluminum material after anodizing meets the requirements.

[0010] The second method is to test the metal structure of different areas of the same aluminum material. If the grain morphology of the tested area is equiaxed and the average grain size is less than 50μm, it indicates that the surface quality of the aluminum material after anodizing meets the requirements.

[0011] Furthermore, when the color difference ΔE of the aluminum material after anodizing is less than 0.25, it indicates that the surface quality of the aluminum material meets the requirements.

[0012] Furthermore, the conductivity fluctuation range of the same piece of aluminum material to be tested should be less than 1MS / m.

[0013] Furthermore, the prediction method is applicable to 5000 series aluminum materials with a Mg content of 0.5 to 6.0 wt.%.

[0014] Beneficial effects:

[0015] (1) The prediction method of the present invention adopts the conductivity or metal structure prediction method for testing under the condition of certain anodizing parameters, wherein: (a) the conductivity prediction method is based on the mean value and range of the conductivity of the aluminum material before anodizing; (b) the metal structure prediction method is to test whether the grain morphology of the aluminum material is equiaxed. The above two methods can be used to predict whether the aluminum material will have color difference defects on the surface after anodizing.

[0016] (2) For 5000 series aluminum materials, the conductivity range is 19 to 26 MS / m, and the conductivity fluctuation range of the same aluminum material is less than 1 MS / m. The smaller the color difference of the anodized surface, the higher the yield rate.

[0017] (3) The present invention determines in advance whether color difference defects will appear on the surface of the aluminum material after anodizing based on the electrical conductivity or metal structure of the aluminum material before anodizing. The prediction method of the present invention is faster and more efficient, avoids material waste, and improves the industrial production yield.

[0018] (4) The prediction method of the present invention is applicable to aluminum materials used for exterior decoration of products such as automobile decoration, curtain wall panels, and consumer electronics, and has fast detection speed and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the grain morphology and distribution diagram of the aluminum plate in Example 1 of the present invention.

[0020] Figure 2This is the grain morphology and distribution diagram of the aluminum plate in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0022] A method for predicting the surface quality of anodized aluminum materials, which is applicable to 5000 series aluminum materials with a Mg content of 0.5 to 6.0 wt.%, and the method is any one of the following two:

[0023] The first method: Use a four-probe conductivity meter to detect the conductivity of different areas of the same aluminum material to be tested, and calculate the conductivity mean A and conductivity range B based on the obtained conductivity values. If A and B respectively meet the following conditions: 19.0MS / m≤A≤26.5MS / m, B<0.5MS / m, and the conductivity fluctuation range of the same aluminum material to be tested is less than 1MS / m, it indicates that the surface quality of the aluminum material after anodizing meets the requirements;

[0024] The second method is to test the metal structure of different areas of the same aluminum material. If the grain morphology of the tested area is equiaxed and the average grain size is less than 50μm, it indicates that the surface quality of the aluminum material after anodizing meets the requirements.

[0025] It should be noted that, since the metal structure test is more complicated, the second prediction method is generally used for smaller aluminum materials (such as when the size of the aluminum material is the same as that of A4 paper), and the first prediction method can be applied to aluminum materials of various sizes.

[0026] It should be explained that the first conductivity prediction method in the present invention is related to the second metal structure prediction method. When the grain morphology of the aluminum material to be tested is equiaxed and the average grain size is less than 50μm, its conductivity mean A and conductivity range B will definitely satisfy: 19.0MS / m≤A≤26.5MS / m, B<0.5MS / m.

[0027] When the color difference ΔE of the aluminum material after anodizing is less than 0.25, it indicates that the surface quality of the aluminum material meets the requirements.

[0028] It should be noted that the specific calculation method of color difference is as follows: (1) Use a colorimeter to quantify the color difference of the anodized aluminum surface, and use a colorimeter to measure the L, a, and b values ​​of the anodized aluminum surface, where "L" represents the brightness of the object: 0-100 represents from black to white; "a" represents the red and green color of the object: positive values ​​represent red, and negative values ​​represent green; "b" represents the yellow and blue color of the object: positive values ​​represent yellow, and negative values ​​represent blue, ΔL=L 样品 -L 标准 , Δa=a 样品 -a 标准 , Δb=b 样品 -b 标准 ; (2) Using the formula Calculate the color difference ΔE.

[0029] The following embodiments all adopt the conductivity prediction method as the main judgment method, and use the metal structure and color difference value as the inspection method for verification, so as to demonstrate the correctness of the prediction method of the present invention.

[0030] Example 1

[0031] A method for predicting the surface quality of anodized aluminum materials, the alloy composition of the aluminum materials used is shown in Table 1. The preparation steps include: smelting, casting, soaking, hot rolling, cold rolling and other processes to prepare the plate. The test results show that the mean value A of the conductivity is 26.16MS / m, the range value B is 0.34MS / m, A and B respectively meet: 19.0MS / m≤A≤26.5MS / m, B<0.5MS / m, and the surface quality of the aluminum material is preliminarily determined to be qualified.

[0032] At the same time, the aluminum metal structure obtained by testing is as follows Figure 1 As shown in the figure, it can be seen that the grain morphology is equiaxed crystal with an average size of 19 μm. The test shows that the surface color difference of the aluminum material after anodizing treatment is ΔE=0.23<0.25, and it is finally determined that the surface quality of the aluminum material meets the technical requirements of the appearance decoration parts.

[0033] Example 2

[0034] A method for predicting the surface quality of anodized aluminum materials, the alloy composition of the aluminum materials used is shown in Table 1. The preparation steps include: smelting, casting, soaking, hot rolling, cold rolling and other processes to prepare the plate. The test results show that the average conductivity is 23.49MS / m, the range is 0.31MS / m<0.5MS / m, and the surface quality of the aluminum material is preliminarily determined to be qualified.

[0035] At the same time, the grain morphology of the aluminum material obtained by the test is equiaxed crystal with an average size of 42μm. After anodizing treatment, the surface color difference of the aluminum material is ΔE=0.19, and A and B respectively satisfy: 19.0MS / m≤A≤26.5MS / m, B<0.5MS / m. Finally, it is determined that the surface quality of the aluminum material meets the technical requirements of exterior decorative parts.

[0036] Example 3

[0037] A method for predicting the surface color quality of anodized aluminum materials, the alloy composition of the aluminum materials used is shown in Table 1. The preparation steps include: smelting, casting, soaking, hot rolling, cold rolling and other processes to prepare the plate. The test results show that the average conductivity is 19.21MS / m, the range is 0.24MS / m, A and B respectively meet: 19.0MS / m≤A≤26.5MS / m, B<0.5MS / m, and the surface quality of the aluminum material is preliminarily determined to be qualified.

[0038] At the same time, the aluminum material obtained by the test has an equiaxed grain morphology with an average size of 12 μm. The surface color difference ΔE of the aluminum material after anodizing treatment is 0.22<0.25. It is finally determined that the surface quality of the aluminum material meets the technical requirements of exterior decorative parts.

[0039] Comparative Example 1

[0040] The aluminum material with the same composition as Example 1 has an average conductivity of 26.41MS / m and a range of 0.65MS / m>0.5MS / m. It is preliminarily determined that the surface quality of the aluminum material is unqualified.

[0041] Aluminum metal structure Figure 2 As shown, the grain morphology is long strip-shaped deformed grains.

[0042] The surface color difference of the aluminum material after anodizing treatment was ΔE=0.56>0.25, and it was finally determined that the surface quality of the aluminum material did not meet the technical requirements for exterior decorative parts.

[0043] Comparative Example 2

[0044] The aluminum material with the same composition as Example 2 was tested and found to have an average conductivity of 24.45 MS / m, with a range of 0.59 MS / m>0.5 MS / m. It was preliminarily determined that the surface quality of the aluminum material was unqualified.

[0045] The grain morphology of the aluminum material is long deformed grains. After anodizing treatment, the surface color difference of the aluminum material is ΔE=0.52>0.25. It is finally determined that the surface quality of the aluminum material does not meet the technical requirements of the appearance decorative parts.

[0046] Comparative Example 3

[0047] The aluminum material with the same composition as Example 3 was tested and its average conductivity was 19.77MS / m, with a range of 0.70MS / m>0.5MS / m. It was preliminarily determined that the surface quality of the aluminum material was unqualified.

[0048] The grain morphology of the aluminum material is long deformed grains. After anodizing treatment, the surface color difference of the aluminum material is ΔE=0.62>0.25. It is finally determined that the surface quality of the aluminum material does not meet the technical requirements of the appearance decorative parts.

[0049] Table 1 Composition of aluminum materials used in Examples 1-3 and Comparative Examples 1-3

[0050]

[0051]

[0052] The prediction method of the present invention constructs the correlation between the metal structure, electrical conductivity and color difference of the anodized surface of aluminum material. The color difference defects of the anodized surface can be predicted through electrical conductivity or metal structure, thus avoiding material waste and improving the industrial finished product rate.

[0053] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for predicting the surface quality of anodized aluminum material, characterized in that: The prediction method is any one of the following two: The first method: Use a four-probe conductivity meter to test the conductivity of different areas of the same aluminum material to be tested, and calculate the conductivity mean A and conductivity range B based on the obtained conductivity values. If A and B respectively meet the following conditions: 19.0 MS / m≤A≤26.5 MS / m, B<0.5 MS / m, it indicates that the surface quality of the aluminum material after anodizing meets the requirements; The second method: testing the metal structure of different areas of the same aluminum material to be tested. If the grain morphology of the tested area is equiaxed and the average grain size is less than 50μm, it indicates that the surface quality of the aluminum material after anodizing meets the requirements; This prediction method is applicable to aluminum materials with components of Si 0.04%, Fe 0.05%, Cu 0.06%, Mn 0.01%, Mg 1.6%, Cr0.01%, Zn 0.02%, Ti 0.02%, and the balance Al; or; This prediction method is applicable to aluminum materials with components of Si 0.08%, Fe 0.18%, Cu 0.01%, Mn 0.02%, Mg 2.6%, Cr0.17%, Zn 0.01%, Ti 0.08%, and the balance Al; or; This prediction method is applicable to aluminum materials with the components of Si 0.02%, Fe 0.03%, Cu 0.03%, Mn 0.01%, Mg 5.8%, Cr0.14%, Zn 0.14%, Ti 0.01%, and the balance Al.

Citation Information

Patent Citations

  • Aluminum product with excellent surface quality and preparing method thereof

    CN108149171A

  • Preparation method of 7000-series aluminum material

    CN112159944A

  • Anodic oxidation aluminum plate with excellent surface quality after thinning and preparation method thereof

    CN114182144A